Comparison between proximal femoral nail and proximal femoral nail antirotation in Peritrochanteric fracture of femur - Kathayat, Tufansingh; Rokaya, Poojan K; Rawal, Mangal; Gurung, Subash; Dutta, Deepak (Journal of Karnali Academy of Health Sciences, 2021)
Introduction: With increasing life expectancy of people, the incidence of peritrochanteric fractures has increased significantly. In the management of unstable peritrochanteric fractures intramedullary devices have proven advantage over extra-medullary ones. Proximal femoral nail antirotation (PFNA) is believed to be better in term of stability, rotational stability and lower cut out rate than proximal femoral nail (PFN), but is still controversial. This study was undertaken to compare the duration of surgery, intraoperative blood loss and duration of C arm fluoroscopy exposure, position of implant, varus collapse and screw cutout, and functional outcome via Harris Hip Score (HHS) between the intramedullary devices.Method: This was a prospective observational study conducted in patients with diagnosis peritrochanteric fractures treated either with PFN and PFNA in National Trauma Center and Civil Services Hospital from 1st May 2018 to 30th November 2019. Out of 48 patients, 24 in each group were included who met the inclusion criteria. Both the groups were followed at 1 month, 3 month and 6 month and were compared in term demographic variables, postoperative complication, and functional outcome via HHS.Result: PFNA has better outcome than PFN in term of mean operative time (48.33±17.2 vs 74.16±21.9 minutes), mean blood loss (80.41±32.19 vs 138.75±45.90 millilitre) and duration of fluoroscopy exposure (48.33±17.29 vs 74.16±21.95 second) respectively. The postoperative varus collapse and screw cut out were higher in PFN than PFNA. The HHS at 6 month follow up of PFNA group had better result than PFN with P < 0.001 (86.12±5.16 vs 75.16±10.11 respectively).Conclusion: PFNA is better in reducing operative time, blood loss, and duration of fluoroscopy exposure. Postoperative complication is comparable but the functional outcome at 6 months follow-up of PFNA is better thanPFN